2020
DOI: 10.14742/ajet.5751
|View full text |Cite
|
Sign up to set email alerts
|

The generation of student engagement as a cognition-affect-behaviour process in a Twitter learning experience

Abstract: Twitter is a microblog that allows users to interact about a topic in online discussion. This makes it an interesting interactive tool with possibilities to increase student engagement and learning performance through active collaboration in an informal learning environment. However, few articles take a quantitative approach to investigate the creation of student engagement using this social networking site. To address this gap, we propose a series of activities conducted through Twitter to analyse the engagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Research points out that motivated students have more opportunities for achieving higher learning performance levels, contributing to enhanced student knowledge through peer interaction, interaction with their instructors, and the study of course materials (Blasco-Arcas et al, 2013 ; Pérez-López et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Research points out that motivated students have more opportunities for achieving higher learning performance levels, contributing to enhanced student knowledge through peer interaction, interaction with their instructors, and the study of course materials (Blasco-Arcas et al, 2013 ; Pérez-López et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the cognitive dimension, the use of new technologies enhances the student experience and has a positive impact on collaborative learning (Pérez-López et al, 2020 ). Several examples of technological use can be provided from this perspective, such as social media, which is commonly used to enhance cognitive engagement among students and between students and their instructors.…”
Section: Model Of Human Attitude Factors Affecting the Adoption Of DImentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of sentiment evolution in blended learning, ENA models showed a significant and positive tendency (e.g., positive sentiments) on sentiment formation at the beginning of blended learning. As the learning process progressed, the findings from ENA showed that the connections among positive-confused, negative-insightful, negative-joking and positive-joking changed significantly with the increase in blended learning activities over time (Garcia et al, 2016;Pérez-López et al, 2020). As suggested by Huang et al (2019), the periods of sentiment evolution were divided into the initial, collision and sublimation, and stable periods.…”
Section: Sentiment Evolution With Different Learning Stages Of Blended Learningmentioning
confidence: 96%
“…Moreover, some researchers considered social interactions to examine the sequences of multiple interactions during the process of knowledge construction (Huang et al, 2019). In the interaction process, students' sentiments are dynamic and unfold over time in blended learning contexts (Pérez-López et al, 2020). Therefore, the interaction process cannot be fully understood without examining sentiments embodied in interactions (Garcia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%